Fecal Biomarkers of Intestinal Health and Disease in Children - Pang, Tamara; Leach, Steven T.; Katz, Tamarah; Day, Andrew S.; Ooi, (Keith) Chee Y. (Frontiers in Pediatrics, 2014)
The identification of various faecal biomarkers has provided insight into the intestinal milieu. Most of these markers are associated with the innate immune system of the gut, apart from the more novel M2-pyruvate kinase (M2-PK). The innate immunity of the gut plays a role in maintaining a fine balance between tolerance to commensal bacteria and immune response to potential pathogens. It is a complex system, which comprises of multiple elements, including antimicrobial peptides (e.g. defensins, cathelicidins, lactoferrin and osteoprotegerin), inflammatory proteins (e.g. calprotectin and S100A12), and microbial products (e.g. short-chain fatty acids). Dysfunction of any component can lead to the development of intestinal disease, and different diseases have been associated with different faecal levels of these biomarkers. Stool quantification of these biomarkers therefore provides a non- invasive method that can assist in the assessment and diagnosis of various gastrointestinal conditions. This can potentially reduce the need for invasive procedures such as endoscopy. The abovementioned faecal biomarkers and their role in intestinal health and disease will be reviewed in this paper with a paediatric focus.